Regulation of Lipid Metabolism by Lamin in Mutation-Related Diseases - Peng, Yue; Tang, Qianyu; Xiao, Fan; Fu, Nian (Frontiers in Pharmacology, 2022)
Nuclear lamins, known as type 5 intermediate fibers, is characterized by fibrous proteins in the nucleus composing structural nuclear membranes and directing transcription. Nuclear lamins are composed of lamin A, lamin C, lamin B1 and lamin B2, which are encoded by LMNA gene and LMNB genes, respectively. Intriguingly, lamin-associated lipid disorders also participate in the occurrence and development of diseases, mainly including familial partial lipodystrophy, mandibular sacral dysplasia, Hutchinson-Gilford progeria syndrome, metabolic associated fatty liver disease, autosomal dominant leukodystrophy, Barraquer-Simons syndrome, atypical Werner syndrome, limb girdle muscular dystrophy, and the autosomal dominant form of Emery-Dreifuss muscular dystrophy. Among those diseases, the regulatory mechanism of nuclear lamins has been widely discussed. Therefore, this review focuses on the role and regulatory mechanism of the nuclear lamins in lipid-related human diseases. Considering the protean actions of nuclear lamins, targeting nuclear lamins may be a potent therapeutic avenue for lipid metabolic disorders and human diseases in the future.